2018
DOI: 10.1093/jac/dky291
|View full text |Cite
|
Sign up to set email alerts
|

FRI-4 carbapenemase-producing Enterobacter cloacae complex isolated in Tokyo, Japan

Abstract: The FRI-4-producing E. cloacae complex was isolated in Japan, whereas all other FRI variants have been found in Europe, suggesting that the spread of FRI carbapenemases is global.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…In 2010, the CDC reported the first carriage of NDM-1-producing E. cloacae in patients previously treated in India (208,209). Recently, metallo-␤-lactamases that comprise IMP-type enzymes and NDM-, GIM-, VIM-, and serine-carbapenemasetype KPC and FRI have been characterized (24,210,211). OXA-48-type serine carbapenemase seems to be the most prevalent (206,212).…”
Section: Molecular Mechanisms Of Resistancementioning
confidence: 99%
“…In 2010, the CDC reported the first carriage of NDM-1-producing E. cloacae in patients previously treated in India (208,209). Recently, metallo-␤-lactamases that comprise IMP-type enzymes and NDM-, GIM-, VIM-, and serine-carbapenemasetype KPC and FRI have been characterized (24,210,211). OXA-48-type serine carbapenemase seems to be the most prevalent (206,212).…”
Section: Molecular Mechanisms Of Resistancementioning
confidence: 99%
“…Limited reports on FRI-type carbapenemases have been published since its description in 2015 and include those from the United Kingdom (FRI-2), 4 Germany (FRI-3), 5 Japan (FRI-4, FRI-5, FRI-8), 6–8 and Canada (FRI-6). 9 In addition, a report from 2019 described a novel carbapenemase FLC-1 (FRI-like carbapenemase) that shared 87% amino acid similarity to FRI-5 10 and 99% similarity to FRI-8.…”
Section: Brief Reportmentioning
confidence: 99%
“…Pulsed-field gel electrophoresis using an S1-nuclease-digested DNA plug (S1-PFGE) showed that TA6363 carried three plasmids (Fig. 1), with the second larger one (pTMTA63632; ∼90 kbp) harboring the novel bla IMP gene according to sequencing plasmids extracted from the S1-PFGE gel (MiSeq; Illumina, San Diego, CA, USA) (9, 10). We found that this bla IMP gene encoded a Ser262Gly point mutant of IMP-11 metallo-β-lactamase, and we named this novel variant “ bla IMP-68 ” (see Fig.…”
Section: Observationmentioning
confidence: 99%
“…Additionally, we tested bla IMP-11 for comparison, and conjugation transfer was tested using E. coli J53, as previously described (9). The MICs of β-lactams were determined by the dry strip method using Etest.…”
Section: Observationmentioning
confidence: 99%